Long-term effects of repeated maternal separation and ethanol intake on HPA axis responsiveness in adult rats - Odeon, Maria Mercedes (2017)
It has been shown that early life manipulations produce behavioral, neural, and hormonal effects. The long term consequences of repeated maternal separation (RMS) plus cold stress and ethanol intake were evaluated during adolescence and adult rats on hypothalamic-pituitary-adrenal (HPA) axis in male adult Wistar rats. RMS+ cold stress was applied from postnatal day (PD) 2 in which the pups were separated from their mothers and exposed to cold stress (4 °C) 1 h per day for 20 days; controls remained with their mothers. Then they were exposed to either voluntary ethanol (6%) or dextrose (1%) intake for 7 days: PD22-29 and PD59-66. Half of the animals were sacrificed, while the others were exposed to acute stress (AS) for 2 h and then they were killed. RMS+ cold stress: a) increased voluntary ethanol intake in adolescent and adult rats; b) reduced protein expression (Western measurements) in corticotropin-releasing hormone (CRH) in hypothalamus (Hyp) and mineralocorticoid receptor (MR) in hippocampus (Hic) while increased glucocorticoid receptor (GR) in Hic; c) decreased plasmatic levels of adrenocorticotropic hormone (ACTH) and increased corticosterone (COR) levels in HPA axis, d) adult rats exposure a new AS incremented ACTH and COR levels. However, this modification did not alter the HPA axis capacity to respond to a new type of stressor. These results demonstrate the consequences of early life stress on the vulnerability of ethanol consumption and HPA axis responsiveness to a stressor in adult rats.